Distinct tumor genomic signatures underlie canine macrophage polarization - Rachel V. Brady; Sunetra Das; Dawn L. Duval; Kristen B. Farrell; Eric P. Palmer; Douglas H. Thamm (PLoS ONE, 2026)
Tumor-associated macrophages (TAMs) drive cancer progression and metastasis. However, the mechanisms by which tumor cells shape TAM phenotypes in canine cancers remain poorly understood. We investigated correlations between cancer cell gene expression and macrophage polarization to identify potential biomarkers and therapeutic targets. Tumor-conditioned media from 25 canine cancer cell lines were applied to monocyte-derived macrophages from three canine donors for 24 hours. Following washout, supernatants were analyzed for immunomodulatory cytokines and chemokines. Each cell line’s polarization capacity was ranked using modified z-scores, then correlated with RNA-sequencing data through Spearman’s correlation and differential expression analysis. Cancer cell lines showed marked heterogeneity in macrophage polarization capacity, largely independent of histologic type. MVB12A, a gene involved in exosome biogenesis, strongly correlated with vascular endothelial growth factor (VEGF) stimulation, suggesting exosome-mediated polarization mechanisms. Exosome fractionation experiments confirmed that purified exosomes induced significantly more macrophage VEGF secretion than other conditions, and high- MVB12A cell lines showed greater VEGF enrichment in exosomes. C-C motif chemokine ligand 3 ( CCL3) was strongly correlated with tumor necrosis factor-alpha (TNF-α) secretion exclusively in histiocytic sarcoma cells, and recombinant CCL3 induced dose-dependent TNF-α secretion from macrophages. High-polarizing cell lines exhibited upregulation of macrophage activation, epithelial-to-mesenchymal transition (EMT), and metabolic reprogramming genes, and downregulation of immune surveillance and cell adhesion genes. Gene set enrichment analysis confirmed pathways for immune suppression, EMT, and extracellular matrix remodeling. These findings identify exosome-associated VEGF stimulation as a previously uncharacterized mechanism in canine tumors and highlight CCL3 as a potential histiocytic sarcoma-specific driver of macrophage TNF-α secretion. Further validation in canine clinical cohorts will determine whether these pathways can serve as biomarkers or therapeutic targets in veterinary oncology.